2017
DOI: 10.1016/j.scitotenv.2017.01.185
|View full text |Cite
|
Sign up to set email alerts
|

Air-water exchange of PAHs and OPAHs at a superfund mega-site

Abstract: Chemical fate is a concern at environmentally contaminated sites, but characterizing that fate can be difficult. Identifying and quantifying the movement of chemicals at the air-water interface are important steps in characterizing chemical fate. Superfund sites are often suspected sources of air pollution due to legacy sediment and water contamination. A quantitative assessment of polycyclic aromatic hydrocarbons (PAHs) and oxygenated PAH (OPAHs) diffusive flux in a river system that contains a Superfund Mega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…At the same time, it is expected that currently unidentified oxygenated PAH compounds will continue to emerge as relevant factors impacting site risk and management, and continued collaboration which supports sharing of compound mass spectral libraries and reference compounds will be needed. Santos et al, 2017Qiao et al, 2014Tidwell et al, 2017 (Siemers et al, 2015), or more variable response to OPAH (Qiao et al, 2013) • Recovery of PAH may be improved by the inclusion of C18 column in the protocol (Motorykin et al, 2015) Lichrolut EN Siemers et al, 2015 Motorykin et al, 2015 OHPAH, PAH deconjugated urine C. Additional nonpolar sorbents : Cyclohexyl, Phenyl, C8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it is expected that currently unidentified oxygenated PAH compounds will continue to emerge as relevant factors impacting site risk and management, and continued collaboration which supports sharing of compound mass spectral libraries and reference compounds will be needed. Santos et al, 2017Qiao et al, 2014Tidwell et al, 2017 (Siemers et al, 2015), or more variable response to OPAH (Qiao et al, 2013) • Recovery of PAH may be improved by the inclusion of C18 column in the protocol (Motorykin et al, 2015) Lichrolut EN Siemers et al, 2015 Motorykin et al, 2015 OHPAH, PAH deconjugated urine C. Additional nonpolar sorbents : Cyclohexyl, Phenyl, C8…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence now challenges the commonly-held assumption that because of their greater polarity, mobility, and bioavailability, oxygenated PAH are inherently more quickly degraded in the environment and are therefore less concerning than parent PAH (Lundstedt et al, 2007). Concentrations of OPAH that exceed parent PAH have been reported by several studies in both soil and water matrices (Bandowe et al, 2014;Brorström-Lundén et al, 2010;Kurihara et al, 2005;McKinney et al, 1999;Tidwell et al, 2017;Wilcke et al, 2014b). In several cases, studies have also demonstrated lower removal rates of some, though not all, of these compounds compared to the parent PAH (Hu et al, 2014), or have demonstrated similar stability to PAH under common environmental conditions (McKinney et al, 1999).…”
Section: Oxygenated Pah and Pah Metabolites In The Environmentmentioning
confidence: 99%
“…Increasingly, passive sampling techniques are used to estimate the air-water exchange of SVOCs. For example, air-water exchange of PCBs and PAHs have been determined in the Lower Great Lakes (Liu et al, 2016), the Lower Duwamish waterway, Washington (Apell and Gschwend, 2017), the Gulf of Mexico (Tidwell et al, 2016), and the Willamette River, Oregon (Tidwell et al, 2017). These studies found that a passive sampling approach improves the spatial resolution, as well as allows direct determination of the freely-dissolved phase of the compounds both in the air and water compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are contaminants that are commonly found in water, soil, and airborne particulates and are converted into various toxic derivatives upon degradation [ 1 , 2 , 3 ]. Natural weathering, photolysis, and biochemical transformations afford oxygenated PAHs (OPAHs) [ 4 , 5 , 6 , 7 ]. On the basis of detailed soil pollutant analyses, Sehlin [ 8 ] concluded that the natural weathering of contaminated soil can result in the OPAH and PAH contents remaining at high levels for long periods; it was also demonstrated that the incomplete biochemical degradation and conversion of PAHs in contaminated soil or water leads to OPAH generation and accumulation.…”
Section: Introductionmentioning
confidence: 99%